PERBEDAAN ANGKA KEJADIAN FISTEL URETROKUTAN PADA PENGGUNAAN KATETER URETRA DAN KATETER SUPRAPUBIK DENGAN STENT SETELAH OPERASI HIPOSPADIA - Sigumonrong, Yacobda H; Santoso, Adi; Djojodimedjo, Tarmono; P, Widodo J (Indonesian Urological Association, 2016)
Objectives: To study rate of urethrocutaneous fistula formation associated with usage of indwelling urethral catheter compared to suprapubic catheter with stent after hypospadias repair. Materials and methods: Twenty patients with primary hypospadias of penile shaft and posterior type underwent reconstruction with onlay technique by a single operator. Urinary diversion in 10 patients utilised a urethral catheter, while the remainder used a silicone suprapubic catheter with stent. Results: Seven urethrocutaneous fistula were observed (35%) with 4 fistulas in the group with suprapubic catheter and stent, and 3 fistulas in the group with urethral catheters. Fisher exact test value was 0,001 with significance level of 1,000 (p>0,05). Conclusion: There was no difference in rate of urethrocutaneous fistula with use of urethral catheter and suprapubic catheterisation with stent after hypospadias repair.